Energy transfer converter between electric vehicles: DC–DC converter based on virtual power model predictive control - Wang, Rui (2023)
Recently, with the deterioration of global climate and the shortage of traditional fossil energy, electric vehicles have been got more attention at present. However, due to the lack of charging piles, the range anxiety regarding electric vehicles become an important pain point, which affects the development of electric vehicles. Based on this, this paper proposes one DC-DC converter using virtual power based model predictive control (VP-MPC), which can provide the energy mutual aid function between two electric vehicles. Firstly, the bidirectional full bridge series resonant DC-DC converter (BDB-SRC) is applied to satisfy the demand high voltage gain and high power density. Meanwhile, this structure also has portable advantages. Furthermore, the different types of electric vehicles have variable parameters, such as load parameters during charging. To solve this problem, VP-MPC is proposed for DC-DC converter. Finally, the simulation and experiment results are provided to verify the high performance of the proposed energy transfer converter between two electric vehicles.